Analisis model pembangunan pertanian di Desa Jaten Kecamatan Jaten Kabupaten Karanganyar - Syah, Elang Imantiar Al Fawwaz; Akbar, Fadhil Ichwan Al; Pramudita, Galuh; Meutiashifa, Nanda Izwin; Purba, Vita Mutiara Rizky (Journal of Biopesticides and Agriculture Technology, 2024)
Background: The ongoing development of agriculture has not succeeded in elevating farmers and agriculture to their proper position. The gap in the welfare of farmers compared to workers in other sectors is indeed widening. Findings: Progress in the agricultural sector will be realized if development planners, in this case the government, are serious about managing the existing natural potential and can improve the welfare of agricultural managers. Agricultural modernization is absolutely necessary for progress in agricultural development because modernization is one of the requirements to be able to compete and improve the quality of agricultural products. Methods: A qualitative approach is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. The descriptive-qualitative research method focuses on problems based on facts carried out by means of observation, interviews, and studying documents. Conclusion: The potential of Jaten Village that can be developed is PAD. The main livelihood of the majority of the Jaten village population is in the non-agricultural sector. The technology in Jaten Village is already very good. The internet network in Jaten Village is very easily accessible.